A influência do comportamento intraempreendedor dos profissionais de projetos e da cultura organizacional intraempreendedora no sucesso de projetos - Elias, Tatiana Carneiro da Cunha de (2019)
Intrapreneurship is increasingly relevant in organizations due to the need for innovation and creativity in the competitive market. Intrapreneurship has been explored in scientific literature for over 30 years. However, its relationship with other concepts, such as project success, remains untapped. The aim of this study is to identify whether intrapreneurial behavior of project professionals and corporate entrepreneurship culture has any influence on project success. The quantitative approach was used through a survey using scales validated by previous studies. The structural equation modeling technique was used for data analysis. The final sample had a total of 284 respondents composed of Brazilian professionals working with projects, but not necessarily as project manager. The results indicate that intrapreneurship of project professionals plays role in project success. Team size or the role of project manager did not moderate this influence, confirming the relevance that any team member's intrapreneurship can influence project success. Despite that, the corporate entrepreneurship culture negatively moderated the relationship of intrapreneurship and project success, showing a decreasing negative effect. This was confirmed when the corporate entrepreneurship culture is low or medium level, but there is no influence on the relationship when the culture is high. On the other hand, corporate entrepreneurship culture could influence directly project success. The most relevant theoretical contribution of this research is to present a new approach to project analysis, considering the behavior of each team member in the success of the project, opening the discussion. Besides that, this study is broadening the discussion of the connection between intrapreneurship and project success by highlighting the level of corporate entrepreneurship culture that may diminish the influence of intrapreneurship on project success. The practical contributions of this research are presenting the importance of identifying the connection between project professionals intrapreneurs with a higher degree of project success in organizations; broadening the discussions of how the corporate entrepreneurship culture is able to influence professionals to work more proactively and innovatively on projects and how much this culture should or should not be influenced in companies that work with projects.